Conduction disturbances after TAVR - a 1-year follow-up. (24th May 2021) - Alves Pinto, R; Proenca, T; Martins Carvalho, M; Torres, S; Grilo, PD; Resende, CX; Amador, AF; Calvao, J; Costa, C; Oliveira, S; Pestana, G; Lebreiro, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Transcatheter aortic valve replacement (TAVR) is an established procedure to treat patients (pts) with symptomatic severe aortic stenosis. Although conduction disturbances remain the most frequent complication, there is a lack of consensus on their management, which leads to significant differences in permanent pacemaker (PPM) implantation rates between centers. Purpose: To evaluate new conduction disturbances and PPM implantation in pts undergoing TAVR, peri-procedure and up to 1 year. Methods: We retrospectively analyzed all pts who underwent TAVR at a tertiary center from October 2014 to November 2019; pts with a previous PPM were excluded (n = 30). Clinical and ECG data were collected at presentation and up to 1 year after implantation, including systematic interrogation of implanted PPM. Results: 340 pts underwent TAVR (57% female, mean age 80 ± 8years). CoreValve Evolut R was the most used valve (41% of pts), followed by CoreValve Evolut Pro (21%) and Acurate Neo (13%). Of the 77% pts who were in sinus rhythm pre-TAVR, 79% had normal atrioventricular (AV) conduction and 20% 1st degree AV block (AVB); 60% had no intraventricular (IV) conduction disturbance, 9% left bundle branch block (LBBB), 7% right bundle branch block (RBBB) and 7% RBBB plus fascicular block. After TAVR, 50.9% of pts exhibited new conduction disturbances. Regarding AV conduction, 12.4% of pts developed advanced AVB and 20% of pts without previous disturbances developed 1st degree AVB. Concerning IV conduction, the most frequent disturbance was de novo LBBB (n = 109, 32, 2%) which resolved in 56% of cases after 6 months. Among pts with previous RBBB, 42% developed advanced AVB; the presence of previous RBBB was the major risk factor for advanced AVB [OR = 8.5 (95% CI 4.1-17.5; p < 0.001)] and PPM implantation [OR = 5.2 (95% CI 2.7-10.0; p < 0.001)], followed by previous 1st degree AVB [OR = 2.3 (95% CI 1.2-4.4; p = 0.016) for PPM implantation]; previous FA or LBBB were not associated with advanced AVB or PPM implantation. Overall, 19% of pts implanted a PPM post-TAVR (n = 63). The main reason was advanced AVB (60%), followed by LBBB plus 1st degree AVB (22%), isolated LBBB (5%) and alternating bundle branch block (ABBB) (5%). At first PPM evaluation, pts with advanced AVB had a median percentage of ventricular pacing (VP) of 80% (52% had VP >90% and 14% <1%) and one year after-TAVR the median percentage of VP was 83%. Concerning pts with LBBB plus 1st degree AVB, median VP at first assessment was 4% (38% had < 1% of VP). In pts with isolated LBBB or ABBB, median VP at first evaluation was 13% and 11%, respectively. Conclusion: LBBB was the most frequent de novo conduction disturbance after TAVR, with more than half of the cases resolving in the first 6 months. RBBB, on the other hand, was the major risk factor for advanced AVB and PPM implantation. Advanced AVB was associated with a high percentage of VP at 1-year follow-up, unlike pts with milder degrees of conduction delay.